Granular cell tumour of the common bile duct. Issue 732 (October 1986) - Cheslyn-Curtis, S.; Russell, R. C.; Rode, J.; Dhillon, A. P.
Abstract : Granular cell tumors are a rare cause of benign biliary stricture. A case is reported which is unusual in that the diagnosis was made before the onset of jaundice. We emphasize the importance of accurate histology of biliary strictures, to eliminate confusion between those of benign and malignant nature and to ensure that the appropriate management is undertaken. Immunohistochemical evidence for the neural origin of this rare tumour is presented.